Laser welding simulation of large-scale assembly module of stainless steel side-wall - Yana Li; Yangfan Wang; Xingfu Yin; Zeyang Zhang (Heliyon, 2023)
Due to the advantageous characteristics of laser welding technology, it is being increasingly used for constructing stainless steel rail vehicles. It can improve the appearance of a vehicle, enable designs with a relatively high degree of flatness, and ensure higher-quality connections between different parts of a vehicle. Moreover, it can improve the strength and stiffness of the components of the vehicle. In this study, a large-scale assembly module of a stainless steel side-wall was considered as the research object. The combined heat source model of a Gaussian heat source and a cylindrical volume heat source was used to obtain the heat source parameters of laser welding to match the experimental data. Based on the thermal cycle curve method (TCCM), the influence of the number of weld segments and mesh divisions of the local model on the efficiency and accuracy of laser welding simulations was investigated. Thereafter, the research results were applied to the welding simulation of the whole side-wall module. The shape of the molten pool obtained using the combined heat source was closer to that of the experiments (error < 10%), demonstrating the accuracy and effectiveness of the developed the heat source model for laser welding simulation. For local model laser welding using the TCCM, a coarse mesh was used, and the weld was divided into four segments, and highly accurate results were obtained. This calculation time was only 5.97% of that of a moving heat source in case of the thermo-elastic-plastic method (TEPM). Residual stress and welding deformation of the stainless steel side-wall module were calculated according to actual process parameters and the results of local model simulation. Residual stress was discontinuously distributed at the weld segments, and it only slightly influenced the overall stress distribution. The maximum residual stress (462.15 MPa) occurred at the weld of the large crossbeam. Welding eight small and two large crossbeams influenced the deformation change and the maximum deformation (1.26 mm) appeared in the middle position of the left side-wall. The findings of this study show that the TCCM has high calculation accuracy and is sufficiently economical for predicting laser welding of large structures.